STRATEGI KOMUNIKASI PERSUASIF PEKERJA SOSIAL DALAM PEMBINAAN REMAJA PUTUS SEKOLAH DI PANTI SOSIAL BINA REMAJA (PSBR) RUMBAI - Karomah, Latifa; Awza, Rusmadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Every region in Indonesia has natural resources of each one of them in the province of Riau. However, social issues such as education still can not overcome. Panti Sosial Bina Remaja (PSBR) Rumbai an orphanage that provides social services in the field of development and social skills to teenagers who dropped out of school. This study aims to determine the methods used by social workers to conduct persuasive communication strategies to clients, knowing the strategies used by social workers in coaching clients, and knowing the barriers experienced by social workers when persuasive communication strategies to clients. This study uses qualitative descriptive study, with the selection of informants using purposive and Snowball theory . The collection data techniques are using observation, interviews, and documentation. The analysis data technique, referring to the interactive model Huberman and Miles. Where as examination of the validity of data using triangulation techniques and the extension of participation. The results of this study indicate that the communication strategy persuasive Social Workers in panti Sosial Bina Remaja ( PSBR) Rumbai done emotionally and rationally, take into account the client's environment, stages purport clien and predict the way of thinking that is most familiar use by persuasive target, The method used is a method of social case work and social group work. The obstacles encountered by social workers to conduct persuasive communication strategy is because of motivation in klien, and noise caused by the noise.Keywords: communication strategies, persuasive communication, social workers, youth fostering drop out of school, Panti Sosial Bina Remaja (PSBR) Rumbai